Private companies in the Russian space industry: features of functioning and development factors - E. A. Efimova (Вестник университета)
The object of the study are private companies which do their business in the Russian space industry. Statistical data on private space companies in Russia based on which the study was conducted, were collected by the author from open sources on the Internet. The purpose of research is to develop recommendations for improving the conditions for the development of private companies operating in the Russian space industry based on an analysis of their characteristics and environmental development factors. In the research, the author used methods of analysis and synthesis, methods of system and comparative analysis, statistical and graphical methods. Research results are the next: the article analyzes the main economic indicators of the Russian and foreign private space companies. The author identifies four main features of the Russian private companies in comparison with foreign ones, which functioning in the space industry. Author proposes a classification of environmental factors that contribute to and restrain the development of private space sector in Russia. Based on the results of the analysis, the author has developed recommendations for improving the economic and legal conditions for the development of Russian private companies in the space industry.